2019
DOI: 10.1080/1331677x.2019.1637763
|View full text |Cite
|
Sign up to set email alerts
|

Does the purchasing power parity fit for China?

Abstract: This paper aims to assess whether the purchasing power parity (PPP) holds by examining the dynamic link between nominal exchange rate (NER) and relative consumer price (RCP) in China. With economic transitions and structural changes existing, we discover that by using full sample data the PPP does not hold. Consequently, we apply the rolling window causality method in order to reconsider the dynamic causal link, and as a result we observe NER having both positive and negative impacts on RCP in some sub-periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Yun (2017 found that the financial channel was an element that led to divergences of the real exchange rate from its long-term reality. Wan et al, (2019) showed that when there exist structural changes, the PPP did not hold for China. Anjaly and Malabika (2021) indicated that the PPP was invalid for the Indian economy.…”
Section: Previous Researchmentioning
confidence: 99%
“…Yun (2017 found that the financial channel was an element that led to divergences of the real exchange rate from its long-term reality. Wan et al, (2019) showed that when there exist structural changes, the PPP did not hold for China. Anjaly and Malabika (2021) indicated that the PPP was invalid for the Indian economy.…”
Section: Previous Researchmentioning
confidence: 99%
“…On the one hand, China's tax policy has improved the VAT chain. By changing business tax to VAT, this policy reduces double taxation, lowers the tax burden on enterprises, stimulates enterprise investment, promotes industrial structure optimization and upgrading, and improves the efficiency of enterprise operation (Wang and Su, 2019) [21]. At the same time, it can increase corporate cash flow, ease internal financing constraints by increasing corporate net profit, and facilitate corporate R&D and innovation activities.…”
Section: Tax Cut Policy and High-quality Development Of Enterprisesmentioning
confidence: 99%
“…According to the results of the Fourier ADF (FADF-SB) test developed by Furuoka (2017), it has been determined that the PPP theory is valid for 16 developing countries, including Turkey. Wang et al (2019), evaluated whether purchasing power parity (PPP) is valid in China by examining the dynamic link between the nominal exchange rate (NER) and the relative consumer price (RCP) and found that PPP is not valid in China. The sliding window causality method was applied for the dynamic causality connection and as a result, they observed that the nominal exchange rate had both positive and negative effects on the relative consumer price in some subperiods.…”
Section: Literature Reviewmentioning
confidence: 99%